Thiosulphate assisted phytoextraction of mercury contaminated soils at the Wanshan Mercury Mining District, Southwest China - J Wang; X Feng; C W N Anderson (Brawijaya University, 2013)
Wanshan, known as the “Mercury Capital” of China, is located in the Southwest of China. Due to the extensive mining and smelting works in the Wanshan area, the local ecosystem has been serious contaminated with mercury. In the present study, a number of soil samples were taken from the Wanshan mercury mining area and the mercury fractionations in soils were analyzed using sequential extraction procedure technique. The obtained results showed that the dominate mercury fractions (represent 95% of total mercury) were residual and organic bound mercury. A field trial was conducted in a mercury polluted farmland at the Wanshan mercury mine. Four plant species Brassica juncea Czern. et Coss.var. ASKYC (ASKYC), Brassica juncea Czern. et Coss.var.DPDH (DPDH), Brassica juncea Czern. et Coss.var.CHBD(CHBD), Brassica juncea Czern. et Coss.var.LDZY (LDZY) were tested their ability to extract mercury from soil with thiosulphate amendment. The results indicated that the mercury concentration in the roots and shoots of the four plants were significantly increased with thiosulphate treatment. The mercury phytoextraction yield of ASKYC, DPDH, CHBD and LDZY were 92, 526, 294 and 129 g/ha, respectively.